Mobile phone usage pattern among undergraduate medical students at a Medical College of Kolkata, West Bengal, India - Bobby Paul; Sima Roy; Indranil Saha; Raghunath Misra; Sita Chattopadhyay; Mausumi Basu (Turkish Society of Public Health Specialists, 2014)
Abstract Objective: Mobile phone usage has reached all ages across all segments of society, and its radiofrequency waves are an increasing concern among the general population. To find out the pattern of mobile phone usage among undergraduate medical students and their perceived symptoms and awareness about negative health effects due to their exposure to the radiofrequency waves. Methods: A descriptive type of epidemiological study was conducted among 295 undergraduate medical students in the Institute of Post Graduate Medical Education and Research, Kolkata, in August 2012 after obtaining Institutional Ethical Clearance. Data were collected by a pre-designed and pre-tested, semi structured questionnaire and analyzed with SPSS software, version 19.0. Results: Among the 1st semester students, browsing of the internet became the predominant activity; while listening to music and radio was the preferred activity among the 3rd, 5th and 7th semester students. In lecture class, 1st semester students (62.5%) switch off; 40.6% of 5th semester students receive and 63.63% of 7th semester students keep the phone in silence mode. Duration of mobile phone usage was maximum among students who perceived headache as a side effect of usage. About 62.3% study subjects cited accidents as a harmful effect, followed by lack of concentration. Conclusions: Regulatory bodies should lay down specific regulations and guidelines regarding mobile phone usage in class as well as during patient care. Further research is needed to comment on long term health outcome keeping in view its usage and popularity among younger people. Keywords: Mobile phone use, medical students, hazard awareness